The role of agriculture and biofortification in the UN Decade of Action on Nutrition - Bouis, Howarth E. (United Nations Systems Standing Committee on Nutrition, 2017)
This article focuses on biofortification, which adds to the supply of minerals and vitamins provided by agriculture by increasing the density of bioavailable nutrients in staple foods. To fully understand and appreciate the role of agriculture in the UN Decade of Action on Nutrition, and the potential impact and comparative advantages of biofortification, this article examines the trends and economic factors that are driving diets in developing countries, in particular, the intakes of food groups that provide dietary quality - legumes, vegetables, fruits and animal-source foods, which are dense in bioavailable minerals and vitamins. The advantages and drawbacks with respect to the more established interventions in addressing mineral and vitamin deficiencies are discussed briefly, followed by a more detailed discussion of biofortification. It is suggested that, to reach its full potential, biofortification must be integrated as a core activity within a range of global actions such as creating policies, partnerships, and funding biofortification-focused crop breeding programmes.